Empowerment of Parents with Stunting Children - Indanah Indanah; Dessie Wanda; Nani Nurhaeni (Universitas Aisyah Pringsewu, 2022)
Stunting is a chronic nutritional problem facing the world. Parental empowerment is necessary for stunting prevention. The main goal of this paper is to systematically review the literature to identify parental empowerment interventions and interventions to improve nutritional status in children, especially stunted children. This Systematic Review uses the PRISMA method, identifies articles published in English, in the last five years (2017 to 2022) through data based on ClinicalKey, ProQuest, SAGE Journal, Scopus, Science Direct, JSTOR, and EBSCO Host, and produces eight relevant literature. The results show a significant relationship between parental empowerment and the nutritional status of children. Parental empowerment is an effort to improve knowledge and skills as well as parents' self-confidence about the care, upbringing, and development of children. Indicators of parental empowerment are assessed based on education, employment, income, and parents' ability to make decisions. Interventions to improve the ability of mothers in the care of stunted children can be carried out through the assistance of health workers in the parenting process. Interventions to improve children's nutritional status through education to mothers about nutrition and nutrition delivery strategies, independently and across sectors. Z score from WHO is the most relevant nutritional status assessment indicator used. Abstrak: Stunting merupakan permasalahan gizi kronik yang dihadapi dunia. Pemberdayaan orangtua diperlukan untuk pencegahan stunting. Penulisan artikel bertujuan menganalisis dengan systematic review untuk mengidenfikasi intervensi pemberdayaan orangtua dan intervensi untuk memperbaiki status nutrisi pada anak, terutama anak stunting. Systematic Review ini menggunakan metode PRISMA, mengidentifikasi artikel yang diterbitkan dalam bahasa inggris, kurun waktu 5 tahun terkahir (2017 sd 2022) melalui data based ClinicalKey, ProQuest, SAGE Journal, Scopus, Science Direct, JSTOR dan EBSCO Host, dan menghasilkan 8 literatur yang relevan. Hasil dari analisis yang dilakukan mengidentifikasi ada hubungan yang signifikan antara pemberdayaan orangtua dengan status gizi anak. Pemberdayaan orangtua merupakan upaya untuk meningkatkan pengetahuan dan ketrampilan serta rasa percaya diri orangtua tentang perawatan, pengasuhan dan perkembangan anak. Indikator pemberdayaan orangtua dinilai berdasarkan pendidikan, pekerjaan, penghasilan dan kemampuan orangtua dalam pengambilan keputusan. Intervensi untuk meningkatkan kemampuan ibu dalam pengasuhan anak stunting dapat dilakukan melalui pendampingan petugas kesehatan dalam proses pengasuhan. Intervensi untuk memperbaiki status nutrisi anak melaui pendidikan pada ibu tentang nutrisi dan strategi pemberian nutrisi, secara mandiri maupun lintas sectoral. Z score dari WHO merupakan indicator penilaian status gizi yang paling relevan digunakan.